Breaking bad. The complete second season [videorecording (DVD)] - Cranston, Bryan, 1956-; Cranston, Bryan, 1956-; Gunn, Anna, 1968-; Mitte, R. J.; Paul, Aaron, 1979- (Sony Pictures Home Entertainment, 2010)
After an unremarkable chemistry teacher learns he has terminal cancer, he turns to an exciting life of crime to provide for his loved ones.